Using digital assessment technology to detect neuropsychological problems in primary care settings - Libon, David J.; Matusz, Emily Frances; Cosentino, Stephanie; Price, Catherine C.; Swenson, Rod; Vermeulen, Meagan; Ginsberg, Terrie Beth; Okoli-Umeweni, Adaora Obiageli; Powell, Leonard; Nagele, Robert; Tobyne, Sean; Gomes-Osman, Joyce Rios; et al. (Frontiers in Psychology, 2023)
INTRODUCTION: Screening for neurocognitive impairment and psychological distress in ambulatory primary and specialty care medical settings is an increasing necessity (Mattke et al., 2022). The Core Cognitive EvaluationTM (CCE) is administered/ scored using an iPad, requires approximately 8 minutes, assesses 3- word free recall and clock drawing to command and copy, asks questions about lifestyle and health, and queries for psychological distress. This information is linked with patients’ self- reported concerns about memory and their cardiovascular risks. METHODS: 199 ambulatory patients were screened with the CCE as part of their routine medical care. The CCE provides several summary indices, and scores on 44 individual digital clock variables across command and copy tests conditions. RESULTS: Subjective memory concerns were endorsed by 41% of participants. Approximately 31% of participants reported psychological distress involving loneliness, anxiety, or depression. Patients with self-reported memory concerns scored lower on a combined delay 3- word/ clock drawing index (p< 0.016), the total summary clock drawing command/ copy score (p< 0.050), and clock drawing to command Drawing Efficiency (p< 0.036) and Simple and Complex Motor (p< 0.029) indices. Patients treated for diabetes and atherosclerotic cardiovascular disease (ASCVD) scored lower on selected CCE outcome measures (p< 0.035). Factor analyses suggest that approximately 10 underlying variables can explain digital clock drawing performance. DISCUSSION: The CCE is a powerful neurocognitive assessment tool that is sensitive to patient’s subjective concerns about possible decline in memory, mood symptoms, possible cognitive impairment, and cardiovascular risk. iPad administration ensures total reliability for test administration and scoring. The CCE is easily deployable in outpatient ambulatory primary care settings.